Metallic Nanodot Patterns with Unique Symmetries Templated from ABC Triblock Terpolymer Networks. Issue 7 (16th January 2018) - Aissou, Karim; Mumtaz, Muhammad; Alvarez‐Fernandez, Alberto; Mercat, Jean; Antoine, Ségolène; Pécastaings, Gilles; Ponsinet, Virginie; Dobrzynski, Cécile; Fleury, Guillaume; Hadziioannou, Georges
Abstract: Nanotemplates derived from the self‐assembly of AB‐type block copolymers provide an elegant route to achieve well‐defined metallic dot arrays, even if the variety of pattern symmetries is restricted due to the limited number of structures offered by microphase separated diblock copolymers. A strategy that relies on the use of complex network structures accessible through the self‐assembly of linear ABC‐type terpolymers is presented for the formation of metallic nanodots arrays with "outside‐the‐box" symmetries. Patterned templates formed by the cubic Q 214 and orthorhombic O 70 network structures are used as excellent platforms to build well‐ordered gold nanodot arrays with unique p 3 m 1 and p 2 symmetries, respectively. A simple yet efficient blending strategy is used to tune the critical dimensions of the p 3 m 1 pattern while laterally ordered gold nanodot arrays are also demonstrated through a directed self‐assembly approach. Such highly ordered gold nanodots with tunable particle dimensions and array periods, enabling the control of their plasmonic responses, are attractive probes for biological imaging. Abstract : Nanotemplates derived from the self‐assembly of linear ABC‐type terpolymers are used to achieve well‐defined metallic dot arrays with "outside‐the‐box" symmetries. Following this strategy, highly ordered gold nanodot arrays with unique p 3 m 1 and p 2 symmetries are demonstrated from patterned templates formed by thin‐film cubic Q 214 and orthorhombic O 70 network structures.